2022
DOI: 10.3389/fphy.2022.1069985
|View full text |Cite|
|
Sign up to set email alerts
|

Multiclass classification using quantum convolutional neural networks with hybrid quantum-classical learning

Abstract: Multiclass classification is of great interest for various applications, for example, it is a common task in computer vision, where one needs to categorize an image into three or more classes. Here we propose a quantum machine learning approach based on quantum convolutional neural networks for solving the multiclass classification problem. The corresponding learning procedure is implemented via TensorFlowQuantum as a hybrid quantum-classical (variational) model, where quantum output results are fed to the sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…This potential arises from the unique features of quantum computing, such as superposition and entanglement, which can provide an exponential speedup for specific machine learning tasks [17]. QML algorithms produce probabilistic results, which align well with classification problems [18]. They also operate in an exponentially larger search space, which has the potential to enhance their performance [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential arises from the unique features of quantum computing, such as superposition and entanglement, which can provide an exponential speedup for specific machine learning tasks [17]. QML algorithms produce probabilistic results, which align well with classification problems [18]. They also operate in an exponentially larger search space, which has the potential to enhance their performance [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of image classification, QML algorithms can process large datasets of images more efficiently than classical algorithms, leading to faster and more accurate classification [24]. Recent studies have also explored hybrid quantum-classical CNNs and demonstrated the classification [18,[25][26][27][28][29][30] and generation [31][32][33][34] of images.…”
Section: Introductionmentioning
confidence: 99%
“…Originally proposed in the context of quantum chemistry [76] and classical optimization problems [28], such algorithms have since found wide use as a tool for leveraging the current generation of noisy, intermediate scale quantum computers [77] to tackle problems which are hard to solve classically. For that purpose they have been extended to a myriad of domains, including machine learning, [1,9,18,27,38,81], preparation of general condensed matter quantum states [29,41,46,79,80,101,105], finance [25,71], molecular biology and biochemisty [10,74], and linear algebra [11,17,106], and have been implemented in numerous quantum simulation platforms [5,34,48,75,102].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent work in quantum machine learning has seen the development of multi-class quantum and quantuminspired classifiers that avoid these heuristic strategies. [9][10][11][12][13][14][15][16] Most recently, the quantum-inspired methods [15,16] use techniques from quantum state discrimination for multi-class classification. Other work has seen the development of quantum convolutional neural networks (QCNNs) for multi-class classification.…”
Section: Introductionmentioning
confidence: 99%
“…Other work has seen the development of quantum convolutional neural networks (QCNNs) for multi-class classification. [9,12] In these methods, a QCNN is trained to reduce the cross entropy loss between its output, interpreted as a probability distribution over all the classes, and the one-hot encodings of the classes.…”
Section: Introductionmentioning
confidence: 99%